Humic Substances: Determining Potential Molecular Regulatory Processes in Plants - Shah, Zahid Hussain; Rehman, Hafiz M.; Akhtar, Tasneem; Alsamadany, Hameed; Hamooh, Bahget T.; Mujtaba, Tahir; Daur, Ihsanullah; Al Zahrani, Yahya; Alzahrani, Hind A. S.; Ali, Shawkat; Yang, Seung H.; Chung, Gyuhwa (Frontiers in Plant Science, 2018)
Humic substances (HS) have considerable effects on soil fertility and crop productivity owing to their unique physiochemical and biochemical properties, and play a vital role in establishing biotic and abiotic interactions within the plant rhizosphere. A comprehensive understanding of the mode of action and tissue distribution of HS is, however, required, as this knowledge could be useful for devising advanced rhizospheric management practices. These substances trigger various molecular processes in plant cells, and can strengthen the plant’s tolerance to various kinds of abiotic stresses. HS manifest their effects in cells through genetic, post-transcriptional, and post-translational modifications of signaling entities that trigger different molecular, biochemical, and physiological processes. Understanding of such fundamental mechanisms will provide a better perspective for defining the cues and signaling crosstalk of HS that mediate various metabolic and hormonal networks operating in plant systems. Various regulatory activities and distribution strategies of HS have been discussed in this review.